PENDUGAAN JUMLAH KARBON TERSIMPAN PADA TEGAKAN JENIS BAKAU (Rhizophora apiculata BL) DI IUPHHK PT. BINA OVIVIPARI SEMESTA KABUPATEN KUBU RAYA - Wiarta, Rinto; Astiani, Dwi; Indrayani, Yuliati; Mulia, Fairus (JURNAL HUTAN LESTARI, 2017)
This study aimed to determine total carbon stock on one to five years old (Rhizophora apiculata BL) trees stand planted in IUPHHK PT. Bina Ovivipari Semesta. This study was conducted over five months on the purposively selected area of forest rehabilitation. This study applied harvested method for 1-3 years old and non-harvested method for 5 years old bakau trees that selected with purposive sampling method. The results showed that the bakau stand has an ability to store very high carbon. The amount of carbon stored in 1 year, 3 years and 5 years of bakau stand were 42.06, 57.93 and 65.91 tonnes ha-1. Keywords: Bakau stand, carbon stocks, Â mangrove ecosystems, PT. Bios